Inorganic fillers influence on the radiation-induced ageing of a space-used silicone elastomer. (June 2016) - Roggero, A.; Dantras, E.; Paulmier, T.; Tonon, C.; Dagras, S.; Lewandowski, S.; Payan, D.
Abstract: A space-used filled silicone rubber (silica and iron oxide fillers) and its polysiloxane isolated matrix were exposed to high energy electrons in order to determine their ageing mechanisms from a structural point of view. Physicochemical analysis evidenced that both filled and unfilled materials predominantly crosslink under such irradiation. Solid-state 29 Si NMR spectroscopy allowed the identification of T-type SiO3 units as the main new crosslinks formed in the polymer network. It also revealed an increase in Q-type SiO4 units in the irradiated filled sample. Thanks to the combination of NMR spectroscopy and ammonia-modified swelling tests, these Q-type units were associated with new crosslinks formed at the silica fillers-matrix interface. While the main interaction between the polysiloxane network and the fillers was shown to proceed mainly through hydrogen bonding in the pristine filled samples, it was suggested that the hydrogen bonds were progressively replaced with SiO4 chemical bonds. These additional chemical crosslinks induced evolutions of the shear modulus on the rubber plateau and crosslink density that were significantly more pronounced in the filled material than in the neat one.